Herlyn–Werner–Wunderlich Syndrome: Case report of a newborn presenting with interlabial cyst. (June 2019) - Cheong, Yee Ling; Laksmi, Narasimhan Kannan
A newborn with Herlyn–Werner–Wunderlich Syndrome presented with interlabial cyst. The cyst was punctured and instilled with contrast medium for cystography to demonstrate the anatomy. Simple resection of the hemivagina septum at the same sitting resolved the obstruction. Early interventions done to clinch diagnosis and institute treatment would help to prevent future complications associated with menses retention and preserve fertility.